All-Cause Mortality Risk of Metabolically Healthy Obese Individuals in NHANES III - Durward, C. M. (Hindawi Publishing Corporation, 2012)
Mortality risk across metabolic health-by-BMI categories in NHANES-III was examined. Metabolic health was defined as: (1) homeostasis model assessment-insulin resistance (HOMA-IR) <2.5; (2) ≤2 Adult Treatment Panel (ATP) III metabolic syndrome criteria; (3) combined definition using ≤1 of the following: HOMA-IR ≥1.95 (or diabetes medications), triglycerides ≥1.7 mmol/L, HDL-C <1.04 mmol/L (males) or <1.30 mmol/L (females), LDL-C ≥2.6 mmol/L, and total cholesterol ≥5.2 mmol/L (or cholesterol-lowering medications). Hazard ratios (HR) for all-cause mortality were estimated with Cox regression models. Nonpregnant women and men were included (n = 4373, mean ± SD, age 37.1 ± 10.9 years, BMI 27.3 ± 5.8 kg/m(2), 49.4% female). Only 40 of 1160 obese individuals were identified as MHO by all definitions. MHO groups had superior levels of clinical risk factors compared to unhealthy individuals but inferior levels compared to healthy lean groups. There was increased risk of all-cause mortality in metabolically unhealthy obese participants regardless of definition (HOMA-IR HR 2.07 (CI 1.3–3.4), P < 0.01; ATP-III HR 1.98 (CI 1.4–2.9), P < 0.001; combined definition HR 2.19 (CI 1.3–3.8), P < 0.01). MHO participants were not significantly different from healthy lean individuals by any definition. While MHO individuals are not at significantly increased risk of all-cause mortality, their clinical risk profile is worse than that of metabolically healthy lean individuals.